Prospects for Collecting Land and Building Tax (PBB) on Raft Houses in the Musi River, Palembang City - Ledy Wila Yustini; Abdul Hamid Usman; Syalwa Rizki Syaqila (LEGAL BRIEF, 2026)
Palembang City is characterized by a geography dominated by waterways, which is reflected in the existence of floating houses along the Musi River as a form of traditional settlement. Floating houses serve important social and economic functions; however, to date they have not obtained legal certainty, particularly in relation to the imposition of Land and Building Tax (Pajak Bumi dan Bangunan/PBB). The main issue lies in the unclear legal status of floating houses as taxable objects, as these structures are built over water and are not attached to land, whereas PBB is generally imposed on land and/or buildings associated with land. This study aims to analyze the prospects for imposing PBB on floating houses along the Musi River in Palembang City, to identify juridical, administrative, and social constraints in their taxation, and to evaluate their potential contribution as a source of Regional Original Revenue (Pendapatan Asli Daerah/PAD). The research employs a sociological (empirical) legal research method, combining normative and empirical approaches through literature review and interviews with local government officials and floating house owners. The findings indicate that, conceptually and normatively, floating houses have the potential to be classified as objects of PBB based on their function and utilization as buildings. However, the implementation of PBB collection has not been carried out optimally due to the absence of specific regulations, limitations in tax object valuation mechanisms suited to the characteristics of floating houses, and social and cultural considerations within the community. Therefore, clear legal arrangements and equitable fiscal policies are required to provide legal certainty and to ensure effective PBB collection on floating houses without disregarding social values and local wisdom